ASUHAN KEPERAWATAN PADA TN. “O” DENGAN SISTEM INTEGUMEN: ABSES INFILTRAT PUNGGUNG KIRI DAN POST DEBRIDEMEN ATAS INDIKASI ABSES DI RUANG DUKU RSUD. DR. ADJIDARMO RANGKASBITUNG – LEBAK - Sarma Eko Natalia Sinaga; Hevi Yolanda Putri Tumanggor (Jurnal Obstretika Scientia, 2014)
The purpose of this research is to gain a real experience, direct, and comprehensive nursing care to Mr.'O‘ who had the integument system disorders: Abscess Infiltrate and Post Debriment over abscess. The indication problems which arose in the presurgery were: pain, infection, and worry. Meanwhile, in post –surgery problems were: acute pain, risk of infection, constipation, self-care deficit, deficiency of knowledge. Intervention was prepared in accordance with existing theory and implementation planning was made to cope the abscesses. Evaluation obtained was nursing diagnosis of acute pain b/d of surgical procedure was resolved within four days, the risk of infection b/d surgical incision partially resolved, constipation b/d post-surgery resolved within two days, self- care deficit b/d pain resolved within one day, and deficiency of knowledge b/d lack of information was overcome within one day.